INTEROPERABILITY CONCEPT OF INDONESIAN NAVY-INDONESIAN COAST GUARD IN NATUNA SEA REGION TO IMPLEMENT TOTAL DEFENSE STRATEGY AT SEA - Pratondo Ario Seno Sudiro (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
Defense is part of Indonesian national purposes mentioned in The Constitution of 1945 “to establish the government of Indonesia to protect all of Indonesian people and Indonesian region”. The Constitution of 1945 also mentioned that every (Indonesian) citizen has right and obligation to join the effort of country defense and security then titled as total defense strategy. There are two great powers in maritime sector. First is Indonesian Navy as the representative of military force and Indonesian Coast Guard as the representative of civilian force. This research aims to formulate interoperability concept between Indonesian Navy and Indonesian Coast Guard based on division of tasks supported by optimization of surveillance equipment in scope of Natuna Sea region using qualitative method. Result of the research is concept of total defense strategy system built from interoperability between Indonesian Navy and Indonesian Coast Guard supported by academician and national defense industry.